Formation of Children's Sports Development System in Rural Areas - Kasimov Akmal; Marasulov Azizbek (Genius Journals, 2023)
In this article, the description, structure, and stages of the work of children's sports schools are described in detail. Sports schools specializing in the preparation of Olympic reserves for children and teenagers are separate or equipped with a sports base and highly qualified coaches-teachers. organization under schools is justified.
Keywords: Children's sports school; sports training, preparatory; study groups and sports to a defined level of skill; the guide-methodologist and the trainers-teachers